Facial synthesis of carbon nanotube interweaved FeOOH as chloride-insertion electrode for highly efficient faradic capacitive deionization - Lu Zhang; Chong, Harry Lye Hin; Dan Luo; Salah M. El-Bahy; Moh Pak Yan; Xingtao Xu; Zeinhom M. El-Bahy (Elsevier B.V., 2024)
Faradic-based capacitive deionization (FDI) has been widely acknowledged as one of the most promising desalination techniques to solve the freshwater crisis, yet was largely limited by heavily trailed development of its anode materials, which subsequently hindered its desalination performance in terms of both desalination capacity and stability. Herein, we developed a new type of anode material for FDI by coupling chloride-insertion FeOOH with carbon nanotubes (CNTs@FeOOH). The essence of this study lay in the composition of FeOOH with CNTs that could not only facilitate charge/electron transfer but also prevent structural aggregation. Consequently, the CNTs@FeOOH-based FDI system displays excellent desalination performance (desalination capacity: 50.36 mg g⁻¹; desalination rate: 0.41 mg g⁻¹ s⁻¹) with robust long-term stability (13.86 % reduction over 80 cycles), which could motivate the future development of other highly-efficient desalination systems.